The International Mobility of Chinese Students: A Cultural Perspective - Liu, Wei (Canadian Journal of Higher Education, 2017)
Anyone hoping to understand China and Chinese people’s behaviour in the present day must examine China’s long history and culture, as these often have crystallized into current behavioural patterns. This paper discusses one important push-out factor for Chinese students’ outbound mobility, and an element that is ignored in many futuristic predictions of international student mobility: traditional Chinese educational culture. I conduct an in-depth analysis of three major aspects of Chinese educational culture in relation to Chinese students’ international mobility: the education-first culture, the saving culture, and the extended-family culture. I argue that these three aspects will continue to drive Chinese students’ outbound mobility.